The Cellular and Molecular Mechanisms of Immuno-Suppression by Human Type 1 Regulatory T Cells - Gregori, Silvia; Goudy, Kevin S.; Roncarolo, Maria Grazia (Frontiers in Immunology, 2012)
The immuno-regulatory mechanisms of IL-10-producing type 1 regulatory T (Tr1) cells have been widely studied over the years. However, several recent discoveries have shed new light on the cellular and molecular mechanisms that human Tr1 cells use to control immune responses and induce tolerance. In this review we outline the well-known and newly discovered regulatory properties of human Tr1 cells and provide an in-depth comparison of the known suppressor mechanisms of Tr1 cells with FOXP3+ Treg. We also highlight the role that Tr1 cells play in promoting and maintaining tolerance in autoimmunity, allergy, and transplantation.